(untitled) (Research, Society and Development, 2020)
Introduction: Futsal is characterized as an intermittent sport modality, which includes technical and tactical skills and cognitive, physical and physiological capacities, those aspects can be influenced by several factors, including sleep. This is considered as a behavioral state of restorative characteristic of the cellular and cognitive aspects, in their respective phases: REM sleep (fast waves) and N-REM sleep (slow waves). Being regulated by the circadian rhythm and the sleep wake cycle. Aim: To verify the subjective quality of sleep of female futsal players. Materials and Methods: The study followed ethical recommendations and has CAAE 04087718.2.0000.5086 from HU-UFMA; For convenience, 9 adult players were selected, with an average age in years of 25.3 ±5.19 with an average body weight in kg of 63.6 ±14.92, average height in centimeters 1.62 ±0,4 and body mass index in Kg/m2 of 23.96 ± 5.05; The subjective quality of sleep was assessed by the Pittsburgh Sleep Quality Index (PSQI-BR); Descriptive statistics. Results and Discussion: The players (100%) had poor sleep quality, an average score of 10.67 ±3.3, lasting for hours of sleep less than 8 hours, an alarming data for a modality that involves high physical and cognitive demands during the game. Conclusion: The players were identified with unsatisfactory sleep and duration below average. It is necessary to take measures that modulate adequate sleep, for a possibility of improvement in performance.